Whipple's disease: the great masquerader—a high level of suspicion is the key to diagnosis - Melas, Nikolaos (BMC Gastroenterol, 2021)
BACKGROUND: Whipple's disease is a chronic infectious disease that primarily affects the small intestine, but several organs can simultaneously be involved. The disease is caused by a gram-positive bacterium called Tropheryma whipplei. The disease is difficult to suspect because it is rare with unspecific and long-term symptoms; it can be lethal if not properly treated. CASE PRESENTATION: We here present three patients who presented with a plethora of symptoms, mainly long-standing seronegative arthritis and gastrointestinal symptoms in the form of diarrhea with blood, weight loss, fever, and lymphadenopathy. They were after extensive investigations diagnosed with Whipple's disease, in two of them as long as 8 years after the first occurrence of joint manifestations. The diagnosis was made by PCR targeting the T. whipplei 16S rRNA gene from small bowel specimen in all three patients, and, besides from histopathologic findings from the duodenum and distal ileum in one and mesenteric lymph nodes in another patient. CONCLUSIONS: This report aims to raise awareness of a very rare disease that presents with a combination of symptoms mimicking other and significantly more common diseases.